The expression rate and prognostic value of phospholipase A2 receptor (PLA2R) in patients with idiopathic membranous glomerulopathy (Journal of Pharmaceutical Negative Results, 2023)
Background and Objective: There are several studies around the world on the prevalence of phospholipase A2 receptor (PLA2R) autoantibodies (Anti-PLA2R) in patients with idiopathic membranous glomerulopathy indicating a wide heterogeneity in expression rate as well as its association with disease outcome. We aimed to determine the incidence of Anti-PLA2R by immunohistochemistry in biopsy of patients with membranous glomerulopathy and its relationship with clinical and pathological features and prognosis of patients.Methods: This cross-sectional study was performed on 198 patients over 18 years of age with membranous glomerulopathy who underwent kidney biopsy from 2009 to 2019. Baseline information as well as data on disease outcome was extracted from patients’ recorded files. Anti-PLA2R was tracked by immunohistochemistry staining in biopsied specimens.Results: PLA2R was expressed in 88.9%. No association was revealed between PLA2R positivity and baseline parameters including gender, age, secondary etiology, positivity of serologic markers, disease stage, the type of glomerulosclerosis, concurrent tubulointerstitial nephritis (TIN) or acute tubular necrosis (ATN), intensity of pathological staining, and the mean of serum biomarkers related to kidney functional state. There was also found no association of PLA2R expression with disease outcome including death, disease recurrence, requiring hemodialysis and recovery rate.Conclusion: Among our selected Iranian patients with membranous glomerulopathy, PLA2R expression is predictable in 88.9% of patients, but it seems that this marker has no prognostic role in these patients in our society.